Uterine inflammatory myofibroblastic tumor: a retrospective analysis - Bai, Liping; Han, Ling; Zheng, Ai (Frontiers in Oncology, 2024)
ObjectiveUterine inflammatory myofibroblastic tumor (UIMT) is a rare tumor of the female reproductive tract with uncertain malignant potential. Previous case series reports have limited our understanding of its diagnosis and treatment. Therefore, we conducted a retrospective analysis of patient files at West China Second University Hospital, Sichuan University to contribute valuable clinical insights to future treatment strategies for this disease.MethodWe comprehensively reviewed patient files of individuals diagnosed with UIMT from January 1st, 2013 to May 1st, 2023.ResultsWe included twenty-seven cases of uterine inflammatory myofibroblastic tumor in our study. Of these, 51.85% (14 cases) were diagnosed with abnormal uterine bleeding, 2 cases had dysmenorrhea, and 12 were unexpectedly diagnosed with suspected uterine fibroids. Ten cases performed total hysterectomy, and 17 cases underwent lesion resection. The positive rate of anaplastic lymphoma kinase (ALK) immunohistochemistry reached 96.3%. After a median of 8 months follow-up time, all patients were disease-free and had survived.ConclusionUterine inflammatory myofibroblastic tumor is easily misdiagnosed, making its diagnosis challenging. Histological features, immunohistochemical results, and molecular confirmation using fluorescence in situ hybridization (FISH) or Next-generation sequencing should be used to confirm the diagnosis. Positive ALK immunohistochemistry, ALK rearrangement, ALK fusion are helpful in diagnosis and ALK inhibitor therapy. Total hysterectomy is often performed for women who do not require fertility, while lesion resection and close follow-up may be considered for those who require fertility preservation.